2017
DOI: 10.18632/oncotarget.16262
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminase inhibitor CB-839 synergizes with carfilzomib in resistant multiple myeloma cells

Abstract: Curative responses in the treatment of multiple myeloma (MM) are limited by the emergence of therapeutic resistance. To address this problem, we set out to identify druggable mechanisms that convey resistance to proteasome inhibitors (PIs; e.g., bortezomib), which are cornerstone agents in the treatment of MM. In isogenic pairs of PI sensitive and resistant cells, we observed stark differences in cellular bioenergetics between the divergent phenotypes. PI resistant cells exhibited increased mitochondrial respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 51 publications
5
91
0
Order By: Relevance
“…Interestingly, we found that upregulation of LIG3 is associated to bortezomib resistance and that LIG3 downregulation is highly toxic and partially restore drug sensitivity in bortezomib-resistant cells. These findings could be consistent with recent evidence which showed that bortezomib resistance in malignant plasmacells is associated to high dependency on increased mitochondrial activity and that mitochondrial activity modulation decreases bortezomib resistance [57][58][59].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we found that upregulation of LIG3 is associated to bortezomib resistance and that LIG3 downregulation is highly toxic and partially restore drug sensitivity in bortezomib-resistant cells. These findings could be consistent with recent evidence which showed that bortezomib resistance in malignant plasmacells is associated to high dependency on increased mitochondrial activity and that mitochondrial activity modulation decreases bortezomib resistance [57][58][59].…”
Section: Discussionsupporting
confidence: 93%
“…The data highlight increased antioxidant capacity, higher redox homeostasis and NAD + levels as the key metabolic changes in PI-resistance and are consistent with findings from earlier models including our own proteomic data. [5][6][7][8][9][10][11][12][13] We functionally validated the increased capacity of PIresistant cells to buffer the formation of reactive oxygen species (ROS), demonstrating 2-to 4-fold lower ROS levels in these cells than in PI-sensitive cells, confirming a significantly higher antioxidant capacity (Figure 2A). Consistent with this, PI-resistant cells are more resistant than PI-sensitive cells to H2O2-induced cytotoxicity (Online Supplementary Figure S4, Online Supplementary Table S2).…”
mentioning
confidence: 82%
“…From a therapeutic perspective, mitochondrial metabolism is an attractive target for treatment regimes, but is not without significant risk of toxicity. Agents which target the mitochondria are potently anti-proliferative, and several small molecules are in clinical trials which inhibit mitochondrial metabolic pathways [14,15,23]. The present study points to a potential complication with this kind of therapeutic strategy however; in that targeting mitochondrial metabolism (e.g.…”
Section: Discussionmentioning
confidence: 77%
“…fluorouracil) have been used clinically for decades [13]. Therapies which target amino acid synthesis are emerging in clinical development, and are showing promise [14][15][16].…”
Section: Introductionmentioning
confidence: 99%